Functional Interference of Sp1 and NF-κB through the Same DNA Binding Site - Hirano, Fuminori (American Society for Microbiology, 1998)
Gene activation by NF-κB/Rel transcription factors is modulated by synergistic or antagonistic interactions with other promoter-bound transcription factors. For example, Sp1 sites are often found in NF-κB-regulated genes, and Sp1 can activate certain promoters in synergism with NF-κB through nonoverlapping binding sites. Here we report that Sp1 acts directly through a subset of NF-κB binding sites. The DNA binding affinity of Sp1 to these NF-κB sites, as determined by their relative dissociation constants and their relative efficiencies as competitor DNAs or as binding site probes, is in the order of that for a consensus GC box Sp1 site. In contrast, NF-κB does not bind to a GC box Sp1 site. Sp1 can activate transcription through immunoglobulin kappa-chain enhancer or P-selectin promoter NF-κB sites. p50 homodimers replace Sp1 from the P-selectin promoter by binding site competition and thereby either inhibit basal Sp1-driven expression or, in concert with Bcl-3, stimulate expression. The interaction of Sp1 with NF-κB sites thus provides a means to keep an elevated basal expression of NF-κB-dependent genes in the absence of activated nuclear NF-κB/Rel.